Influence of social support, stress and coping strategies on depression among children with physical disability in Nigeria (2016)
This study examined the influence of social support, stress and coping strategies on depression among children with physical disability in Nigeria. The study adopted cross sectional research design, purposive sampling technique was used to select 120 children with physical disability and questionnaires were used for data collection. The result of the findings revealed that there was a significant influence of social support on depression {t(118)=4.55; p<.05} and further analysis indicated that participants with low social support experienced higher levels of depression ( Mean = 69.73 ) while participants with high social support experienced lower levels of depression (Mean = 62.22). More so, the finding depicted independent significant influence of stress and coping strategies on depression {β = .68, t = 11.47; P < .05 & β = .289, t = 4.96; p < .05}. Also, the finding depicted joint significant influence of social support, stress and coping strategies on depression {F (3, 116) = 881.39; p < .05}. Therefore, the study concluded that social support, stress and coping strategies are predictors of depression among children with physical disability in Nigeria and recommended that government and non-governmental organisation should endeavour to implement an ecological-based support programme to support, educate and enlighten physically challenged children, their family members and society on how to help the disabled children deals with life situation